2017
DOI: 10.1016/j.ymeth.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Site-selective orientated immobilization of antibodies and conjugates for immunodiagnostics development

Abstract: Immobilized antibody systems are the key to develop efficient diagnostics and separations tools. In the last decade, developments in the field of biomolecular engineering and crosslinker chemistry have greatly influenced the development of this field. With all these new approaches at our disposal, several new immobilization methods have been created to address the main challenges associated with immobilized antibodies. Few of these challenges that we have discussed in this review are mainly associated to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
109
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(122 citation statements)
references
References 226 publications
0
109
0
Order By: Relevance
“…As an extension, we also demonstrated that mCherry‐AzF in cell lysates was efficiently immobilized onto a DBCO‐functionalized well in a plate via SPAAC, indicating general feature of the technique developed here. As reported in literature, the site‐specific immobilization feature of this technique would provide additional advantages, such as orientation control and retained activity, over conventional immobilization techniques. For large‐scale applications, several issues need to be addressed in future.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…As an extension, we also demonstrated that mCherry‐AzF in cell lysates was efficiently immobilized onto a DBCO‐functionalized well in a plate via SPAAC, indicating general feature of the technique developed here. As reported in literature, the site‐specific immobilization feature of this technique would provide additional advantages, such as orientation control and retained activity, over conventional immobilization techniques. For large‐scale applications, several issues need to be addressed in future.…”
Section: Resultsmentioning
confidence: 85%
“…Protein immobilization onto solid supports has been widely utilized for research and industrial processes . Immobilization of antibodies and receptors plays an important role in constructing sensitive biosensors for diagnostics and drug screening . Furthermore, protein immobilization is critical in generating protein arrays for proteomics .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in pH, temperature, and salt concentration can potentially denature affinity proteins; monoclonal‐affinity cell separations are significantly impacted by these environmental changes, whereas pAbs are more robust . Furthermore, the orientation of the antibody affinity ligand and the hydrophobicity of the capture surface also affect cell separation performance .…”
Section: Capture Molecules and Other Ligandsmentioning
confidence: 99%